Lectins Are the Sparkle of Hope for Combating Coronaviruses and the Global COVID-19 - Heba Salah Abbas; Muddukrishnaiah Kotakonda (Tabriz University of Medical Sciences, 2022)
Today the crisis of coronavirus disease 2019 (COVID-19) pandemic represents a threatworldwide because it is a leading cause of human morbidity and mortality. Besides, it possessesa destroying impact on countries' economies. Therefore, there is an urgent need for hardresearch work and global collaboration to find a potential therapy. In this review, structuralgenomic variations in COVID-19 and further therapeutic options of Coronaviridae family orCOVID-19 are expressed. Lectins are natural proteins, which can exist in algae, higher plants,banana, actinomycetes, fungi, and archaea, and they have antiviral properties. Griffithsin lectin,isolated from red algae, has noteworthy efficacy against lethal SARS-CoV infection, humancoronaviruses, and other animal coronaviruses. Furthermore, all mannose-specific plant lectinshave anti-coronaviruses properties except for garlic lectins. However, lectins from mushroomscan act as immunomodulators by activating T-lymphocyte or stimulating dendrites or cytokines.The lectin may hinder glucans on viral spike protein and prevent entry and the virus's release.Lectin's anti-coronavirus activities include a glimmer of hope to tackle the global COVID-19crisis and inspire more scientific work on carbohydrate-binding agents against SARS-CoV-2.